True three-phase bidirectional switch based AC-AC Buck-Boost converter topology - Tanvir Hossain, Mohammad Rubaiyat; Abedin, Amina Hasan; Choudhury, Mohammad Ali A Shoukat; Uddin, Mohammad Nasir (© 2013 IEEE Computer Society, 2016)
This conference paper was presented in the 2013 2nd IEEE Jordan Conference on Applied Electrical Engineering and Computing Technologies, AEECT 2013; Amman; Jordan; 3 December 2013 through 5 December 2013 [© 2013 IEEE Computer Society] The conference paper's definite version is available at: http://doi.org/10.1109/AEECT.2013.6716458